The fixed point set of the inverse involution on a Lie group - Duan, Haibao; Liu, Shali (Topological Methods in Nonlinear Analysis, 2023)
The inverse involution on a Lie group G is the periodic 2 transformation γ that sends each element gG to its inverse g^-1. The variety of the fixed point set (γ ) is of importance for the relevances with Morse function on the Lie group G, and the G-representations of the cyclic group Z_2. In this paper we develop an approach to calculate the diffeomorphism types of the fixed point sets (γ) for the simple Lie groups.